Evaluation of an ESP Textbook Used at the College of Business Studies in Kuwait from the Learners’ Perspective Regarding Their Future Career Needs - Haidar, Nour Haidar (European Scientific Journal, ESJ, 2024)
This study evaluates an English for Specific Purposes textbook used for teaching at the College of Business Studies in Kuwait to assess learners’ perceptions and effectiveness in preparing them for future careers in the business world. The study involved 122 learners enrolled at the college, and ten English language instructors employed there. These objectives were accomplished by using quantitative methods for data collection and analysis. A checklist is prepared for learners to analyze their perspectives on the textbook. This checklist is used in the interviews and the questionnaire to ascertain their points of view. The findings supported the hypothesis that the learners’ perspectives on the textbook were varied. Most learners regarded the textbook as helpful in fulfilling their requirements and preparing them for future employment. However, a minority of learners believed the textbook was unsuitable for their English proficiency. The textbook was particularly beneficial in the reading, listening, and speaking skills. However, it did not adequately focus on developing the writing skills. It provided professional tasks and viewpoints, including expert speakers and real company case studies.